1976
DOI: 10.1177/00220345760550064601
|View full text |Cite
|
Sign up to set email alerts
|

Videotape Modeling of the Child Dental Patient

Abstract: One week before their first dental visit, 36- to 60-month-old children were shown a videotape to model their behavior in the dental situation. The behavior was then rated for three visits. The children who had been modeled did not behave significantly better than either children who had no previous contact with the dental setting or children who had visited the reception room one week before their first dental visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Results of this study revealed that children who had been exposed to watch a video prior to their second treatment session were significantly less anxious "relaxed" and more cooperative "definitely positive to cooperation" comparing to their first dental session. These findings are in accord with that of Fields and Pinkham, 24 and Rouleau et al, 26 where they found that the presentation of a model through a film leads the children to demonstrate relatively little negative behavior towards dental treatment and the film presentation in addition to the procedure of prophylaxis before the film can have a positive impact on the child's acquaintance and dental behaviors. Additionally, findings of this work are in harmony with that of Melamed et al, 23 where they reported that children who were prepared for restorative procedures by watching a filmed peer model harmonize with the particular elements of the treatment session were more cooperative and presented less disruptive behaviors as they experienced similar treatment procedures.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Results of this study revealed that children who had been exposed to watch a video prior to their second treatment session were significantly less anxious "relaxed" and more cooperative "definitely positive to cooperation" comparing to their first dental session. These findings are in accord with that of Fields and Pinkham, 24 and Rouleau et al, 26 where they found that the presentation of a model through a film leads the children to demonstrate relatively little negative behavior towards dental treatment and the film presentation in addition to the procedure of prophylaxis before the film can have a positive impact on the child's acquaintance and dental behaviors. Additionally, findings of this work are in harmony with that of Melamed et al, 23 where they reported that children who were prepared for restorative procedures by watching a filmed peer model harmonize with the particular elements of the treatment session were more cooperative and presented less disruptive behaviors as they experienced similar treatment procedures.…”
Section: Discussionsupporting
confidence: 88%
“…[19][20][21] Several studies have assessed the effectiveness of the modeling through a film in the reduction of child's dental anxiety. [22][23][24][25][26][27][28] It has been revealed that filmed modeling can be effective as well as live modeling in addition to desensitization methods. 22,24 In contrast to the other social learning based methods, filmed modeling does not take time by the dentist and the dental team although it has not achieved its appropriate situation.…”
Section: Ijedsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 According to several studies, FM is proved to be efficient in reducing child's dental treatment anxiety. 13,[21][22][23] It has been shown that FM can be as effective as live modeling and also desensitization methods. 21,23 Contrary to other behavior management techniques, FM does not take much time by the dentist or his team, though it has not gained much attention.…”
Section: Discussionmentioning
confidence: 99%
“…Such a recording is considered as a modeling tool. 28,29 • When the parents are in the operatory, they are not allowed to interfere with the procedure after they have approved and consented to the proposed treatment. Furthermore, the parents should be prepared to leave the dental operatory if the youngster does not cooperate.…”
Section: Parental Presence/absence Technique Protocolmentioning
confidence: 99%